Substrate and Mg doping effects in GaAs nanowires - Kannappan, Perumal; Sedrine, Nabiha Ben; Teixeira, Jennifer P.; Soares, Maria R.; Falcão, Bruno P.; Correia, Maria R.; Cifuentes, Nestor; Viana, Emilson R.; Moreira, Marcus V. B.; Ribeiro, Geraldo M.; de Oliveira, Alfredo G.; González, Juan C.; et al. (Beilstein Journal of Nanotechnology, 2017)
Mg doping of GaAs nanowires has been established as a viable alternative to Be doping in order to achieve p-type electrical conductivity. Although reports on the optical properties are available, few reports exist about the physical properties of intermediate-to-high Mg doping in GaAs nanowires grown by molecular beam epitaxy (MBE) on GaAs(111)B and Si(111) substrates. In this work, we address this topic and present further understanding on the fundamental aspects. As the Mg doping was increased, structural and optical investigations revealed: i) a lower influence of the polytypic nature of the GaAs nanowires on their electronic structure; ii) a considerable reduction of the density of vertical nanowires, which is almost null for growth on Si(111); iii) the occurrence of a higher WZ phase fraction, in particular for growth on Si(111); iv) an increase of the activation energy to release the less bound carrier in the radiative state from nanowires grown on GaAs(111)B; and v) a higher influence of defects on the activation of nonradiative de-excitation channels in the case of nanowires only grown on Si(111). Back-gate field effect transistors were fabricated with individual nanowires and the p-type electrical conductivity was measured with free hole concentration ranging from 2.7 × 1016 cm−3 to 1.4 × 1017 cm−3. The estimated electrical mobility was in the range ≈0.3–39 cm2/Vs and the dominant scattering mechanism is ascribed to the WZ/ZB interfaces. Electrical and optical measurements showed a lower influence of the polytypic structure of the nanowires on their electronic structure. The involvement of Mg in one of the radiative transitions observed for growth on the Si(111) substrate is suggested.
Keywords: electronic structure; field effect transistors; GaAs nanowires; photoluminescence